Relationship between the polymerization distance of monowave and polywave light-curing units and the irradiance and physical properties of dental resin-based composites - Flores-Ledesma, Abigailt; Laura E. Serrano de la Rosa; Ortega, Juana P. Ramírez; Rodríguez-Chávez, Jacqueline A.; Ruiz-Peñarrieta, Madelin; María de los Angeles Moyaho-Bernal; Salazar-Vergara, José A. (Journal of Oral Science, 2024)
Purpose: To evaluate the influence of the polymerization distance of monowave and polywave light curing units (LCUs) on the measured irradiance relative to the value reported by the manufacturer in relation to the physical properties of resin-based composites (RBCs).Methods: Four LCUs were used: one monowave and three polywave. The irradiance was measured with a digital radiometer. Depth of cure (DC) and flexural strength (FS) tests were performed according to ISO 4049:2019 at polymerization distances of 0 mm and 5 mm.Results: The irradiance of all LCUs was higher than that reported by the manufacturer (>25-64%). The irradiance of the four LCUs was reduced when polymerization was performed at between 0 to 5 mm (paired t-test, P < 0.001). The DC at 0 mm was similar in all groups but was significantly decreased at 5 mm distance (ANOVA P < 0.001). FS showed differences among the LCUs at 0 mm (ANOVA P < 0.001) and was affected by the polymerization distance. The elastic modulus was unaffected by the LCU used or the distance (ANOVA P > 0.001).Conclusions: The LCU must be positioned as near as possible to RBCs during the polymerization process, as increased distance negatively affects the depth of cure and flexural strength.